Evaluación técnico-financiera para la implementación de válvulas reguladoras de contrapresión en tubing de 2 7/8", en pozos que presentan interferencia por gas en el Campo Palagua (2018)
The Palagua Field is situated in the Vereda Palagua, jurisdiction of the Puerto Boyacá municipality in the department of Boyacá, along the River Magdalena, to the southwest of the Middle Magdalena Valley Basin, Colombia. It was discovered in november 1954 by the Texas Petroleum Company who drilled the first well, named P-1 and took place the 4th of november of that same year. This well produced 427 BOPD in its official test and its oil had an API gravity of 18.2°. The wells in the Palagua Field are assisted mostly by sucker-rod lift as artificial system. Given the mature nature of the field and the increasing production of gas, it has been observed that there's gas interference in the downhole pump that affects the pump efficiency, obtaining values below 50%. This phenomenon affects daily oil production and makes it necessary to find a solution that allows the pump to fill properly without wasting too much money. This work aims to evaluate the behaviour of backpressure regulator valves in wells with gas interference in order to analyse the impact of backpressure on the pump's efficiency. Thus, three sample wells whose operational conditions allowed for individual analysis of the phenomenon of gas interference were chosen, leaving aside other problems common to the Palagua Field such as sanding and high BS&W.